TRUE UNGULATES FROM THE NAGRI TYPE LOCALITY (LATE MIOCENE), NORTHERN PAKISTAN - M. A. Khan; M. Akhtar; T. Ikram (Journal of Animal and Plant Sciences, 2012)
The early Late Miocene type locality of the Nagri Formation from the Indo-Siwaliks has yielded remains of the true ungulates that are today extinct to the south Asian biogeographic realm. Thirteen species including Brachypotherium, Hipparion, Listriodon and the bovids of the true ungulates from the village Sethi Nagri, district Chakwal, Punjab, Pakistan, are recognized, described and discussed in details. The tooth positions of all thirteen species are documented. Quantitatively, the taxa of the bovids are the most predominant. But Brachypotherium, Hipparion, Listriodon, tragulid and giraffid fossils are approximately as common as each other at the type locality. Pachyportax, Dorcabune, Miotragocerus and Gazella seem to be uniformly rare at Sethi Nagri. The new findings from the type locality are the Giraffokeryx’s hemimandible and the deciduous premolar of Dorcatherium minus. The newly recovered hemimandible and deciduous premolar enlarge our knowledge on the anatomic features of the Nagri true ungulates. The Nagri type locality mammalian local fauna has similarities to late Miocene Eurasian faunas. The investigation comprises extensive taxonomic descriptions of all species represented and an interpretation of the palaeoecology based on an analysis of the community structure. It seems that the abundance of Hipparion, giraffids, rhinocerotids and bovids suggests a woodland to savannah environment at or near the type locality during the early Late Miocene. There is little evidence to suggest that there was a humid closed canopy forest interspersed with temporary and perennial waters and accompanying open areas forest in the vicinity at the time of deposition.
Keywords: Listriodon; Bovidae; Giraffidae; Tragulidae; Hipparion; Brachypotherium; Siwaliks